Treatment of Refinery Industry Wastewater Using Ion Exchange Technology and Studies Kinetics and Thermo-dynamic Parameters - Mohammed, Thamer J.; Habeeb, Saif I.; Kreamid, Zaydoun K.; Ali, Ali A. (Journal of Petroleum Research and Studies, 2018)
A batch system has been used for removal of chloride, sulfate and sodium pollutants from wastewater of Daura refinery. The fine grained resin lewatit was used in this study, batch experiments were performed to examine the effects amount of resin and mixing time on the removal efficiency and residual of pollutants. The kinetics and thermodynamics of adsorption were also analyzed. Various thermodynamic parameters such as enthalpy (ΔH◦), free energy (ΔG◦) and entropy (ΔS◦) showed that the adsorption was endothermic, spontaneous and feasible. The removal efficiency of sulfate, chloride and sodium is (91%, 88%, 82%), respectively. The optimum mixing time is (12min) for sulfate and sodium, and (14 min) for chloride. Sulfate adsorption on lewatit fitted well to the pseudo-second-order kinetic model, but adsorption of chloride and sodium on lewatit behaves to the pseudofirst- order kinetic model.